Application of Bioprocessed SBE Based Biovigorant as Soil Enhancer - Joko Sulistyo; Bambang Gunawan (UNIVED Press, Dehasen University Bengkulu, 2022)
One of efforts to accelerate the process of restoring degraded agricultural lands is to use soil enhancer or soil conditioner in order to create an environment that is conducive to environmental protection, support plant growth and production, development of soil biota, and increase soil resistance to erosion, thus the soil enhancer must have the ability to facilitate optimal supply of nutrients, water and air. This study used a completely randomized design consisting of several treatments, respectively; Control (no soil enhancer), Zeolite (inorganic soil enhancer), and Biovigorant based bioprocessed spent bleaching earth (SBE, organic soil enhancer). The results showed that the biovigorant met the requirements of environmental quality standards based on government regulation and fulfills the technical quality requirements as a soil enhancer with special functions. Although the use of biovigorant may improve the soil chemical properties, however, it does not have a significant impact on agronomic factors. The use of biovigorant did not accumulate heavy metals, such as AS, Hg, Pb, Cd, Cr, Ni towards soil, water, and plants, but has a comparable effect with zeolite regarding with chemical properties and plant growth. As an organic soil enhancer, biovigorant meets all the minimum technical requirements. The use of biovigorant in agricultural crops, especially maize, did not contribute negatively to the accumulation of the heavy metals in the surrounding soil and water, and furthermore, based on mass balance analysis, the biovigorant did not provide the potential for accumulation in the next growing season.